2014
DOI: 10.1007/s00405-014-3377-8
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in bimodal hearing users (unilateral cochlear implants and contralateral hearing aids)

Abstract: The main objective was to evaluate the bimodal self-rated benefits on auditory performance under real conditions and the quality of life in two groups of cochlear-implanted adults, with or without a contralateral hearing aid. The secondary objective was to investigate correlations between the use of a hearing aid and residual hearing on the non-implanted ear. This retrospective study was realized between 2000 and 2010 in two referral centers. A population of 183 postlingually deaf adults, implanted with a coch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
42
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(52 citation statements)
references
References 27 publications
10
42
0
Order By: Relevance
“…Because of this, we cannot conclude whether reductions in loneliness were directly caused by CI or HA use. Although it is fair to speculate that CI recipients received more extensive rehabilitation, this study could not account for the degree of improved aural rehabilitation that each individual achieved with HA or CI use; nor could we account for other factors that impact device effectiveness, including the use of assistive listening devices and bilateral amplification or even total hours of use . We found that HA users missed follow‐up visits more often than CI users.…”
Section: Discussionmentioning
confidence: 88%
“…Because of this, we cannot conclude whether reductions in loneliness were directly caused by CI or HA use. Although it is fair to speculate that CI recipients received more extensive rehabilitation, this study could not account for the degree of improved aural rehabilitation that each individual achieved with HA or CI use; nor could we account for other factors that impact device effectiveness, including the use of assistive listening devices and bilateral amplification or even total hours of use . We found that HA users missed follow‐up visits more often than CI users.…”
Section: Discussionmentioning
confidence: 88%
“…Because we did not include randomization or an untreated control arm, we are unable to definitively say increases in quality of life were directly caused by HA or CI use. We also are not able to investigate the role of determinants of CI and HA effectiveness such as hours of use, assistive listening device use, or unilateral versus bilateral device use . Selection bias and external validity warrant consideration, although this study was completed in a relatively diverse population.…”
Section: Discussionmentioning
confidence: 99%
“…We also are not able to investigate the role of determinants of CI and HA effectiveness such as hours of use, assistive listening device use, or unilateral versus bilateral device use. 35 Selection bias and external validity warrant consideration, although this study was completed in a relatively diverse population. Our analysis was posited on the assumption that data were MAR, but it is possible that those who experienced declines in the quality of life were less likely to attend follow-up visits, or that those who did not attend follow-up visits differed with respect to other potential confounding factors.…”
Section: Discussionmentioning
confidence: 99%
“…The PTA of the continuing HA group (mean = 78 dB HL, median = 82 dB HL) is substantially better than the average hearing loss that has been reported in some previous studies of the characteristics of bimodal device users (e.g., Devocht et al., 2015; Farinetti et al., 2015; Fitzpatrick et al., 2009). Inspection of our data reveals that 62 of the 80 continuing group were implanted between February 2010 and February 2015.…”
Section: Discussionmentioning
confidence: 99%
“…Other retrospective studies also provide evidence that those who discontinue HA use have less residual hearing in the unimplanted ear than those who continue HA use. In two other studies, mean PTA of nonbimodal users exceeded 100 dB HL in the unimplanted ear (e.g., Farinetti et al., 2015; Fitzpatrick et al., 2009). …”
Section: Introductionmentioning
confidence: 89%